Buoyancy induced flow in a nanofluid filled enclosure partially exposed to forced convection - Abu-Nada, Eiyad; Öztop, Hakan Fehmi; Pop, Ioan (Academic Press Ltd- Elsevier Science Ltd, 2012)
A numerical study was performed on natural convection for water-CuO nanofluid filled enclosure where the top surface was partially exposed to convection. The cavity has a square cross-section and differentially heated. Except exposed convection part on the top, all sides are adiabatic on horizontal walls. Effects of Rayleigh number (10(3) <= Ra <= 10(5)), Biot number (0 <= Bi <= infinity), length of partial convection (0.0 <= L <= 1.0) and volume fraction of nanoparticles (0.0 <= phi <= 0.1) on heat and fluid flow were investigated. The results showed that for the case of high Blot number that heat transfer along the heated was enhanced by increasing the Rayleigh number mainly at the upper portion of the heated wall. When the top wall was totally exposed to convection, the results prevail that the heat transfer was more effective at high Biot number especially at the upper portion of the heated wall. For the case of high Biot number, the results prevailed that the heat transfer at the upper portion of the heated wall increases considerably at high exposed length to convection (L); however, for L <= 0.75 the effect of L was less pronounced. Contour maps for percentage of heat transfer enhancement were presented and it was shown that the location of maximum enhancement in heat transfer was sensitive to Ra, phi and L. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Nanofluid; Natural convection; Partially exposed enclosure